Reutilização de fibras de para-aramida como reforço mecânico em poliamida 6,6 - Loureiro, Lucas (Universidade Federal de São Carlos, 2016)
Aramid fibers are very known by their excellent combination of tensile strength and elastic modulus with low density. On the other hand, aramids do not melt which difficult the recycling process. This property is an important issue for many companies that work with these materials since thousands of tons of aramid fibers are produced each year and there are just a few reutilization alternatives. This project evaluated a new alternative to reuse aramid fibers from industrial waste as mechanical reinforcement for polyamide 6,6. Another important characteristic of these fibers is the low interaction with polymeric matrices due to its intrinsic molecular stability and to finishing products that facilitates the spinning and weaving processes. In order to remove the finishing, the fibers were washed with methanol and hexane, but the hexane washed fibers showed better results. Surface treatments with NaOH solutions were also evaluated. It was reported in XPS results that NaOH solution hydrolyzed the fiber’s surface. However, conditions with higher NaOH concentration were too aggressive to the fiber’s mechanical properties. For this reason, it was selected two procedures: 2% NaOH at 30 minutes of exposure and 6% NaOH at 45 minutes of exposure. The composites were produced with two different fiber’s weight concentration, 5 and 10%. The results have shown that the surface treatment impacted the interfacial adhesion, but there was no increase on the composite’s mechanical properties due to the fiber’s mechanical damage caused by the treatment. The addition of 5% of fibers did not increase the mechanical properties probably due to the fact that 5% is near to the fiber’s critical volume for this composite. The composites with 10% of fibers showed better results and revealed a great potential for this reuse alternative for para-aramid fibers.
Reuse of para-aramid fibers as a mechanical reinforcement filler in polyamide 6,6 matrix
Keywords: Fibras de aramida; Reciclagem; Poliamida 6,6; Compósito; Aramid fiber; Recycling; Polyamide 6,6; Composite; CIENCIAS EXATAS E DA TERRA; ENGENHARIAS